2020
DOI: 10.15671/hjbc.639411
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study on Urinary Tract Infection Agents Isolated from Children and Their Antibiotic Susceptibility

Abstract: A ntibiyotikler idrar yolu enfeksiyonlarının tedavisinde önemli bir dayanak noktası olmasına rağmen, bilinçsiz kullanımları antibiyotik direncinin gelişimi için önemli bir risk faktörüdür. Antibiyotik direnci, özellikle çocuk ürolojisinde, artan üropatojen direncinin en önemli sorunlarından bir olarak karşımıza çıkmaktadır. Ampirik reçete uygulamalarındaki eksiklikler bu sorunu daha da kötüleştirmektedir. Bu çalışmada; pediatrik hastaların demografik özellikleri, idrar yolu enfeksiyonu etkenleri ve bu etkenler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…The resistance rates of Klebsiella to ampicillin, AMC, TMP-SMX, cefuroxime, and nitrofurantoin were found to be high, similar to previous studies in the literature [15,18]. In addition, we observed that Klebsiella had low rates of resistance to amikacin and meropenem, which is in agreement with the findings of Duicu et al and İdil et al [13,19]. We found no significant increase in the antibiotic resistance rates of Klebsiella spp.…”
Section: Discussionsupporting
confidence: 92%
“…The resistance rates of Klebsiella to ampicillin, AMC, TMP-SMX, cefuroxime, and nitrofurantoin were found to be high, similar to previous studies in the literature [15,18]. In addition, we observed that Klebsiella had low rates of resistance to amikacin and meropenem, which is in agreement with the findings of Duicu et al and İdil et al [13,19]. We found no significant increase in the antibiotic resistance rates of Klebsiella spp.…”
Section: Discussionsupporting
confidence: 92%
“…In studies conducted in Turkiye, E. coli, Klebsiella spp., and Enterobacter spp. are reported to be the most common pathogens with growth in culture (24)(25)(26). Similar to our study, Bozkurt et al also found that Proteus spp.…”
Section: Sixtysupporting
confidence: 91%
“…Gökçe et al reported that the resistance rate was 71% for ampicillin, 43% for ACA, 31% for trimethoprim/sulfamethoxazole (TMP-SMX), 14% for ceftriaxone, and 4% for amikacin (32). In another study, İdil et al determined the resistance rate as 70.2% for ampicillin, 49% for ACA, and 37.1% for TMP-SMX, 34.2% for ceftriaxone, and 1.3% for amikacin resistance (26). In our study, the resistance rates of ceftriaxone and amikacin were determined as 25.9% and 5.6%, respectively.…”
Section: Sixtymentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Turkish pediatric data were strictly concordant with Eastern European data, and indicated similarly, serious rates of β-lactam resistance, fluoroquinolone, and sulfamethoxazole/trimethoprim resistance. [21][22][23][24][25] Our data were not divided into age groups but in general, compatible levels of AMR were observed.…”
Section: Discussionmentioning
confidence: 92%